Effectiveness of methods for detaching orthodontic implants likely to fracture upon rotational torque – an animal study. Issue 1 (9th February 2016) - Nakagaki, Susumu; Iijima, Masahiro; Yasuda, Yoshitaka; Handa, Keisuke; Koike, Toshiyuki; Saito, Takashi; Mizoguchi, Itaru
Abstract: Orthodontic implants may fracture at the cortical bone level upon rotational torque. The impacted fragment can be detached by a range of methods, which are all more or less time‐consuming and injurious to the cortical bone. The aim of this study was to compare three different methods for detaching an orthodontic implant impacted in cortical bone. Health Sciences University of Hokkaido animal ethics committee approved the study protocol. Orthodontic titanium‐alloy (Ti‐6Al‐4 V) implants were placed bilaterally on the buccal side of the mandible of beagle dogs. Subsequently, the implants were detached using either a low‐speed handpiece with a round bur, alternatively by use of a low‐power or a high‐power ultrasonic instrument. In the first experiment, 56 orthodontic implants were placed into the dissected mandible from 7 animals. The methods for detachment were compared with respect to time interval, as well as associated undesirable bone loss as appraised by use of cone‐beam computed tomography. In experiment two, 2x2 implants were placed bilaterally in the mandible of 8 animals and subsequently detached by manual rotational torque, and the described three methods for detachment. The implant socket was investigated histologically as a function of removal method immediately after removal, and after 1, 3 and 8 weeks and contrasted with the healing of the socket of the implant that was detached by manual rotational torque. Statistical significance was appraised by the use of non‐parametric Kruskal‐Wallis one‐way analysis of variance. The method using the low‐power ultrasonic required significantly longer removal time versus the two other methods, i.e. high‐power ultrasonic and low‐speed handpiece with a round bur (p < 0.02). The amount of undesirable bone loss was substantially larger with low‐speed handpiece with a round bur compared to the two ultrasonic methods (p < 0.05). Bone formation after 3 weeks of healing was more complete following the use of low or high‐power ultrasonic instrument in comparison with a low‐speed handpiece rotary instrument method. Orthodontic implants likely to fracture upon rotational torque or impacted fractured fragments should be detached preferably with an ultrasonic instrument, because of less associated bone loss and more rapid bone healing compared to the use of a low‐speed handpiece rotary instrument.